Orlistat‐induced fulminant hepatic failure. Issue 6 (29th September 2014) - Sall, D.; Wang, J.; Rashkin, M.; Welch, M.; Droege, C.; Schauer, D.
Summary Orlistat was approved by the Food and Drug Administration in 1998 and has been shown to be superior to placebo in achieving weight loss. It is generally well tolerated. However, severe liver injury has been reported. We present a case of hepatic failure in a patient taking orlistat. A 54‐year‐old African‐American woman with hypertension presented with hepatic failure. She had noticed increasing fatigue, jaundice and confusion. She used alcohol sparingly and denied tobacco or illicit drug use, but had been taking over‐the‐counter orlistat for the past two months. Physical examination revealed scleral icterus, jaundice, asterixis and slow speech. Laboratory testing showed markedly abnormal liver function tests with coagulopathy. Acute viral and autoimmune serologies were negative, as was toxicology screen. Liver biopsy showed necrotic hepatic parenchyma likely secondary to drug toxicity. Based upon her clinical presentation and time course, the pattern of liver injury seen on liver biopsy and lack of an alternative plausible explanation, her liver failure was most likely associated with orlistat use. She continued to deteriorate and ultimately underwent orthotopic liver transplantation. Fourteen cases of severe liver injury associated with orlistat use have been reported, four of which are detailed in the literature. This is the second published case of liver failure associated with over‐the‐counter orlistat usage. Clinicians should be aware of the growing number of cases associating liver injury and orlistat use and carefully monitor their patients on this medication for signs of hepatic dysfunction.